Pengujian Fungsionalitas Sistem Administrasi Sekolah Berbasis Web (Administrasi Sekolah Web-App) Metode Blackbox Testing Menggunakan Standar ISO/IEC 29119 - Rivalno Putra Mulya; Muhammad Adib Iktimal; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
Manual management of school administration data involving physical documents or spreadsheets often leads to data inconsistency, potential duplication, and operational inefficiency. The Web-App School Administration System was developed as a web-based solution for managing digital and summarized Student, Teacher, and Subject Data. This study aims to test the system's core functionality. The testing scope includes the authentication module (Login) and CRUD (Create, Read, Update, Delete) operations on master data. The testing method used is Blackbox Testing utilizing Equivalence Partitioning (EP) and Boundary Value Analysis (BVA) techniques. Testing and reporting procedures are implemented in accordance with the principles of the ISO/IEC/IEEE 29119 standard. The test results indicate that the Web-App School Administration System functions according to the specified functional specifications, provides a high level of operational feasibility, and is an effective alternative to replacing conventional school administration procedures.